Implementation Strategies and the Uptake of the World Health Organization Surgical Safety Checklist in Low and Middle Income Countries: A Systematic Review and Meta-analysis. Issue 6 (June 2021) - White, Michelle C.; Peven, Kimberly; Clancy, Olivia; Okonkwo, Ijeoma; Bakolis, Ioannis; Russ, Stephanie; Leather, Andrew J. M.; Sevdalis, Nick
Abstract : Objectives: To identify the implementation strategies used in World Health Organization Surgical Safety Checklist (SSC) uptake in low- and middle-income countries (LMICs); examine any association of implementation strategies with implementation effectiveness; and to assess the clinical impact. Background: The SSC is associated with improved surgical outcomes but effective implementation strategies are poorly understood. Methods: We searched the Cochrane library, MEDLINE, EMBASE and PsycINFO from June 2008 to February 2019 and included primary studies on SSC use in LMICs. Coprimary objectives were identification of implementation strategies used and evaluation of associations between strategies and implementation effectiveness. To assess the clinical impact of the SSC, we estimated overall pooled relative risks for mortality and morbidity. The study was registered on PROSPERO (CRD42018100034). Results: We screened 1562 citations and included 47 papers. Median number of discrete implementation strategies used per study was 4 (IQR: 1–14, range 0–28). No strategies were identified in 12 studies. SSC implementation occurred with high penetration (81%, SD 20%) and fidelity (85%, SD 13%), but we did not detect an association between implementation strategies and implementation outcomes. SSC use was associated with a reduction in mortality (RR 0.77; 95% CI 0.67–0.89), all complications (RR 0.56; 95% CI 0.45–0.71) and infectious complications (RR 0.44; 95% CI 0.37–0.52). Conclusions: The SSC is used with high fidelity and penetration is associated with improved clinical outcomes in LMICs. Implementation appears well supported by a small number of tailored strategies. Further application of implementation science methodology is required among the global surgical community. Abstract : Supplemental Digital Content is available in the text